Electric-magnetic duality in N = 2 supersymmetric gauge theory - Alvarez, José Luis Alejo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this dissertation we present a description of the electric-magnetic duality and their classical and quantum aspects. Our analysis starts from the suggested magnetic monopoles by Dirac in 1931 [1] and goes until the work of Seiberg and Witten in 1994 [27]. In the classical description, we need to introduce the magnetic monopoles in order to make manifest the electricmagnetic duality. Later, the origin of monopoles becomes clear when we start from a Yang-Mills theory. The classical aspects of the E-M duality are covered in the Montonen-Olive conjecture 1977[7]. Working on the quantum aspects of the theory, we note the importance of introducing supersymmetry. Specially for extended supersymmetry, where we take advantage of the holomorphicity property, which leads us to the non-renormalizable theorems, where the computation is easier. We focus on theN = 2SU(2) supersymmetric gauge theories. It turns out that the theory is fully solvable at the low energies regime[27]. Most of this work is based on reviews about the Seiberg and Witten duality [30],[31],[32]

Nesta dissertação apresentamos uma descrição da dualidade elétrica-magnética e seus aspectos clássicos e quânticos. Nosso análise se inicia com os monopolos magéticos sugeridos por Dirac em 1931[1] e vai até o trabalho do Seiberg e Witten em 1994 [27]. Na descrição clássica, precisamos introduzir os monopolos magnéticos a ﬁm de obter a dualidade elétrica-magnética manifesta. Mais tarde, a origem dos monopolos se mais torna mais clara quando começamos com uma teoria de Yang-Mills. Os aspectos clássicos da teoria foram explicados pela conjetura de Montonen e Olive 1977 [7]. Explorando os aspectos quânticos da teoria, notamos a importância de introduzir supersimetria, principalmente supersimetria estendida, onde tiramos vantagem da propiedade de holomorficidade, a qual nos leva aos teoremas não renormalizáveis, onde o cálculo é mais simples. Focamos na teoria de gauge supersimétrica N = 2 SU(2). A teoria é completamente resolvível para baixas energias. A maior parte do conteúdo deste trabalho é baseada nas várias revisões da dualidade de Seiberg-Witten [30],[31],[32]
Keywords: Magnetic monopoles; Monopolos magnéticos; Teoria de Yang-Mills; Supersimetria; Dualidade (Fisica nuclear)